2017
DOI: 10.3389/fped.2017.00189
|View full text |Cite
|
Sign up to set email alerts
|

Management of High-Grade Penile Curvature Associated With Hypospadias in Children

Abstract: Penile curvature is a frequent feature associated with hypospadias with also a great variability of severity among each patient. While the low-grade curvature (<30°) can be relatively easily corrected by simple techniques like penile degloving and dorsal plication, severe cases often demand more complex maneuvers to manage it. A great number of surgical techniques have been developed to adequately correct curvatures greater than 30°; however, each one of them should be individualized to different patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 54 publications
1
21
1
Order By: Relevance
“…In a recent study (182 patients) ( 6 ), the saline erection test performed at the beginning of the operation showed that only 14% of patients had a curvature (≤45°), 54% (45–90°), and 31% (≥90°). This is completely different from the findings reported by Snodgrass and the authors who report “an absence or mild curvature (<30°) in 50% of patients with proximal shaft to perineal hypospadias” ( 7 ).…”
contrasting
confidence: 96%
See 1 more Smart Citation
“…In a recent study (182 patients) ( 6 ), the saline erection test performed at the beginning of the operation showed that only 14% of patients had a curvature (≤45°), 54% (45–90°), and 31% (≥90°). This is completely different from the findings reported by Snodgrass and the authors who report “an absence or mild curvature (<30°) in 50% of patients with proximal shaft to perineal hypospadias” ( 7 ).…”
contrasting
confidence: 96%
“…I agree with the authors who report “It is believed that a curvature greater than 20–25° found in children is significant” ( 7 ) and I believe that a curvature <15–20° can be tolerated in the correction of the curvature. However, the curvature of the penis is an anomaly very often present in the proximal forms of hypospadias.…”
supporting
confidence: 86%
“…Another study proposed that severity of chordee is generally proportional to the degree of hypospadias (19). Many factors, such as abnormal development of the urethral plate, brotic mesenchymal tissue at the urethral meatus, and ventral-dorsal corporal disproportion may be interconnected resulting in different degrees in the nal severity of curvature in each patient (20). Dartos tissue pattern is not in uenced by age.…”
Section: Discussionmentioning
confidence: 99%
“…Another study proposed that the severity of chordee is generally proportional to the degree of hypospadias (19). Many factors, such as abnormal development of the urethral plate, brotic mesenchymal tissue at the urethral meatus, and ventral-dorsal corporal disproportion, may be interconnected, resulting in different degrees in the nal severity of curvature in each patient (20). The Dartos tissue pattern is not in uenced by age.…”
Section: Discussionmentioning
confidence: 99%